Planning and diversity in the city. Redistribution, recognition and encounter. - Fincher, Ruth; Iveson, Kurt (Palgrave Macmillan, 2008)
Planning theory and practice has become more conscious in recent times of the need to cater for a diverse range of needs and preferences. But there has been less clarity about what goals and objectives should inform planning for such diversity. In this book the authors identify three distinct working principles of planning for diversity: redistribution, recognition and encounter. Each principle is the subject of a pair of chapters. The first explaining the principle and the second showcasing and comparing efforts to shape cities according to it, drawing on relevant examples from around the world.
Keywords: Stadtentwicklungsplanung; Stadtplanung; Planungstheorie; Kommunikation; Kooperation; Planungspraxis; Entscheidungsfindung; Diversität; Governance; Fremdheit; Anerkennung; Begegnung; Kinderfreundlichkeit; Umverteilung